Childhood Maltreatment, Low Serum Cortisol Levels, and Non-Suicidal Self-Injury in Young Adults With Major Depressive Disorders - Bo Peng; Bo Peng; Jinmeng Li; Haitao Liu; Han Fang; Han Fang; Weitan Zhao; Weitan Zhao; Guanjie Chen; Guanjie Chen; Meihong Xiu; Yingli Zhang; et al. (Frontiers in Pediatrics, 2022)
BackgroundNon-suicidal self-injury (NSSI) is a serious public health problem widely present among young adults and adolescents. While finding risk factors associated with NSSI among young patients with major depressive disorder (MDD) is challenging, the current study aims to measure childhood adversity and serum cortisol levels and elucidate their relationship in MDD patients with NSSI.MethodsIn this cross-sectional study, 126 young patients with MDD (aged 16 to 35 years) were recruited. The depressive symptoms were assessed by the Beck Depression Inventory (BDI-II), and the childhood adversity was evaluated by the Chinese version of the Childhood Trauma Questionnaire (CTQ) scale. Serum cortisol levels were determined by the kits in patients.ResultsRelative to MDD patients without NSSI, MDD patients with NSSI had a higher CTQ total score and its four subscores. Moreover, the cortisol levels in patients with MDD/NSSI were significantly decreased than in MDD patients without NSSI. For patients with MDD/NSSI, there is a negative association between cortisol levels and emotional neglect, but not for MDD patients without NSSI. Further regression analysis showed that low cortisol levels, BDI-II, and emotional neglect were risk factors for NSSI in young patients with MDD.ConclusionOur findings suggest that young MDD patients with NSSI experience more childhood adversity and have lower cortisol levels. Also, lower cortisol levels were associated with childhood adversity but not with depressive symptoms. Further, lower cortisol levels, depressive symptoms, and emotional neglect were risk factors for NSSI in young patients with MDD.